1993
DOI: 10.1002/j.1460-2075.1993.tb06075.x
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian ribonucleotide reductase R1 mRNA stability under normal and phorbol ester stimulating conditions: involvement of a cis-trans interaction at the 3′ untranslated region.

Abstract: Ribonucleotide reductase R1 gene expression is elevated in BALB/c 3T3 fibroblasts treated with the tumor promoter, 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA). We show that TPA treatment increased the half‐life of R1 mRNA by 5‐fold, indicating that TPA regulates R1 gene expression by a post‐transcriptional mechanism. We investigated the possibility that the 3′ untranslated region (3′UTR) of R1 mRNA contains regulatory information for TPA‐mediated message stability. Our studies demonstrated that a 49 nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 34 publications
5
61
0
Order By: Relevance
“…Interestingly, in one of the original descriptions of PTEN, it was identified as a TGF-b regulated gene (Li and Sun, 1997). RRM1 has an element in the 3 0 -untranslated region that appears to be involved in message stability, and it is responsive to TGF-b (Chen et al, 1993;Amara et al, 1996). It is thus conceivable that the increased levels of RRM1 in H23-R1 cells result in increased availability of a factor that is involved in the regulation of PTEN message.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in one of the original descriptions of PTEN, it was identified as a TGF-b regulated gene (Li and Sun, 1997). RRM1 has an element in the 3 0 -untranslated region that appears to be involved in message stability, and it is responsive to TGF-b (Chen et al, 1993;Amara et al, 1996). It is thus conceivable that the increased levels of RRM1 in H23-R1 cells result in increased availability of a factor that is involved in the regulation of PTEN message.…”
Section: Discussionmentioning
confidence: 99%
“…Akashi et al (2) reported that stabilization of GM-CSF mRNA by PKC activation is mediated by AU-rich sequences. Recently, Chen et al (16) identified a region in the 3'UTR of ribonucleotide reductase R1 mRNA and a protein of 52 to 57 kDa interacting with this region that are involved in TPA-induced stabilization. Stabilization after TPA treatment has also been reported for collagenase (12), interleukin 1 (22), GAP-43 (53), GLUT1 (61), and TGFP1 (65) mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…This was reported to be the result of mRNA stabilization caused by protein binding to a specific regulatory 49-nucleotide element in the 3Ј-UTR of the mRNA. However, no studies on cell cycle-regulated R1 gene expression were reported (13). To study mRNA stabilization as a mechanism for regulating the R1 mRNA levels during the cell cycle, we introduced the putative regulatory 49-mer from the R1 gene into the luciferase reporter gene.…”
Section: Transcriptional Regulation Of the R1 Promoter During Thementioning
confidence: 99%